Kegiatan Ziarah ke Makam Tuan Syekh Silau Laut dalam Pandangan Masyarakat Desa Silo Lama Kecamatan Silau Laut Kabupaten Asahan - Sirait, Reza Rukman; Arifinsyah, Arifinsyah; Zulkarnain, Zulkarnain (Darul Yasin Al Sys, 2023)
This research discusses the pilgrimage activities to the grave of Mr. Sheikh Silau Laut in the view of the community in Silo Lama Village, Silau Laut District, Asahan Regency. The aim of this research is to determine the influence and views of the community and pilgrims regarding the pilgrimage to the grave of Mr. Sheikh Silau Laut. This research method uses a qualitative approach. By using data collection techniques through interviews, observation and documentation. The informants in this research were pilgrims, cemetery administrators and local people who had been selected by researchers according to the research subject criteria. The results of the research show that the grave pilgrimage activities carried out at the Tomb of Mr. Syekh Silau Laut had a positive influence on both the surrounding community and the pilgrims themselves. The community and pilgrims think that the view from the grave pilgrimage carried out by the community makes us always remember death, and makes us diligent in worship, like to give alms, and build friendship. visiting graves will make someone more generous than before, because at this moment they are taught to be sincere and surrender to Allah SWT.